Monitoring the impact of the activities of the Kumtor mining facility on water quality (for example, the Naryn river) (Eurasian Journal of Ecology, 2016)
Industrial enterprises have a significant impact on the environment, the stability of the natural resources. The article presents the results of monitoring of the Naryn river basin.
Keywords: monitoring; water resources; industrial enterprise; the Naryn river; environment